2012
DOI: 10.1080/17470218.2012.679946
|View full text |Cite
|
Sign up to set email alerts
|

Markedness effects in Norwegian–English bilinguals: Task-dependent use of language-specific letters and bigrams

Abstract: This study investigates how bilinguals use sublexical language membership information to speed up their word recognition process in different task situations. Norwegian-English bilinguals performed a Norwegian-English language decision task, a mixed English lexical decision task, or a mixed Norwegian lexical decision task. The mixed lexical decision experiments included words from the nontarget language that required a "no" response. The language specificity of the Bokmål (a Norwegian written norm) and English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
87
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(101 citation statements)
references
References 37 publications
13
87
0
Order By: Relevance
“…In this line, studies using non-words with different degrees of cross-linguistic similarity in their orthographic structure have shown that this factor highly determines how fast and accurately bilingual participants will reject them in lexical decision tasks (e.g., Lemhöfer & Dijkstra, 2004;Lemhöfer & Radach, 2009). While the evidence in this regard is still scarce, the studies testing the impact of orthographic markedness in bilingual visual word processing with bilingual readers whose languages share the same alphabet have demonstrated the importance of sub-lexical orthographic cues (see Casaponsa, Carreiras and Duñabeitia, 2014;Vaid and Frenck-Mestre, 2002;Van 4 Kesteren, Dijkstra, and de Smedt, 2012). The purpose of the present study is to explore whether cross-linguistic orthographic regularities constrain the access to language-specific orthographic and lexical representations in seemingly monolingual language contexts (i.e., single-language tasks).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In this line, studies using non-words with different degrees of cross-linguistic similarity in their orthographic structure have shown that this factor highly determines how fast and accurately bilingual participants will reject them in lexical decision tasks (e.g., Lemhöfer & Dijkstra, 2004;Lemhöfer & Radach, 2009). While the evidence in this regard is still scarce, the studies testing the impact of orthographic markedness in bilingual visual word processing with bilingual readers whose languages share the same alphabet have demonstrated the importance of sub-lexical orthographic cues (see Casaponsa, Carreiras and Duñabeitia, 2014;Vaid and Frenck-Mestre, 2002;Van 4 Kesteren, Dijkstra, and de Smedt, 2012). The purpose of the present study is to explore whether cross-linguistic orthographic regularities constrain the access to language-specific orthographic and lexical representations in seemingly monolingual language contexts (i.e., single-language tasks).…”
mentioning
confidence: 99%
“…Previous studies have shown that bilinguals are highly sensitive to the statistical regularities of words in their two languages and that they use this information in an automatic fashion while reading (see Casaponsa et al, 2014;Vaid & Frenck-Mestre, 2002;Van Kesteren et al, 2012, among others). It thus seems that bilingual readers whose languages share the same script develop fine-grained sensitivity to language-specific sub-lexical information, and that orthotactic cues lead to a different organization of lexical semantic representations for orthographically marked and unmarked words.…”
mentioning
confidence: 99%
See 3 more Smart Citations